The Effect of Financial Technology Use, Lifestyle, Peer Interaction, and Self-Control on Students Personal Financial Management - Rachel Oktaviona; Han Tantri Hardini (JURNAL PENDIDIKAN IPS, 2025)
The purpose of this research was to determine the effect of the use of financial technology, lifestyle, peer interaction, and self-control on the personal management of students of the Faculty of Economics and Business, Universitas Negeri Surabaya. This type of research is explanatory research, with the study subjects being students from the Faculty of Economics and Business, Universitas Negeri Surabaya, specifically the Class of 2021 in the Bachelor of Accounting Education, Bachelor of Accounting, and Bachelor of Management study programs. The sampling technique used was purposive sampling, which involved a total of 188 students. The data analysis technique used multiple linear regression analysis with SPSS 25. The results of the study show that (1) the use of financial technology, lifestyle, peer interaction, and self-control has a simultaneous effect on students' personal financial management. (2) The use of financial technology does not have a significant effect on students' personal financial management. (3) Lifestyle affects students' personal financial management. (4) Peer interaction affects students' personal financial management. (5) Self-control affects students' personal financial management. The adjusted R-squared value in this study was 46.9%, which means that the contribution of the influence of the use of financial technology, lifestyle, peer interaction, and self-control on students' personal financial management was 46.9%. While the remaining 53.1% was influenced by other variables outside this study.